Trends in Outpatient Dental and Oral Visits at Selemadeg Timur I Public Health Center - Pratama, I Wayan Agus Wirya; Dewi, I Gusti Agung Ayu Chandra Iswari; Idaryati, Ni Putu; Pramesti, I Gusti Ayu Ratih (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Oral and dental health problems in Indonesia continue to increase, yet the utilization rate of health services, especially in remote, frontier, and outermost (3T) regions, remains relatively low. Community Health Centers (Puskesmas) play a crucial role in providing promotive, preventive, curative, and rehabilitative services, supported by electronic medical record systems to facilitate the analysis of patient visit patterns and morbidity. This study aims to evaluate the pattern of patient visits to the dental and oral health unit at UPTD Puskesmas Selemadeg Timur I, Megati Village, as a basis for improving the quality and effectiveness of health services. Materials and Methods: This study is descriptive quantitative research conducted at UPTD Puskesmas Selemadeg Timur I in April 2025. Data were collected from the medical records of 1,253 patients from January to December 2024 using a total sampling method. The observed variables included visit classification, payment mechanisms, gender, and 5 dominant cases based on gender. The results were analyzed and presented in tables and charts to illustrate the distribution and trends of dominant cases. Results and Discussion: There were 1,253 visits over one year, with the majority being follow-up patients (73.42%), covered by JKN (91.37%), and female patients (61.77%). The peak of visits occurred in December, influenced by the academic calendar and health promotion activities. The most common diagnosis was pulpitis (K04.0) at 43.66%, disturbances of tooth eruption (K00.6) at 22.27%, gingivitis and periodontal diseases (K05.0) at 22.11%, pulp necrosis (K04.1) at 5.91%, and periapical abscess without sinus (K04.7) at 2.39%. Conclusion: The visits were predominantly follow-up cases, involving JKN participants and female patients, with pulpitis (K04.0) being the most frequent diagnosis. The high utilization of JKN highlights the vital role of community health centers in ensuring equitable access and quality of dental healthcare services in their respective service areas.